2023
DOI: 10.1029/2022ja031142
|View full text |Cite
|
Sign up to set email alerts
|

The 2021 Antarctic Total Eclipse: Ground Magnetometer and GNSS Wave Observations From the 40 Degree Magnetic Meridian

Abstract: Solar eclipses provide an opportunity to study ionospheric dynamics in a way unlike any other. The majority of the sun's direct energy link into Earth's atmosphere is rapidly turned off and on again, and the impact of such a modulation is profound. Anyone who has experienced an eclipse from under the track of totality in person can attest to the dramatic temperature swings that occur from the momentary absence of sunlight. From the perspective of the global atmospheric system, the effects are equally noteworth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Model results from previous studies have shown that conductivity can be reduced by nearly half under the region of totality. This rapid modification of conductivity on the dayside has been associated with magnetosphere-ionosphere waves observed in both hemispheres during a high latitude eclipse (Coyle et al, 2023). It is possible that these dayside magnetosphere waves couple to a fast-mode wave that travels toward the magnetotail.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Model results from previous studies have shown that conductivity can be reduced by nearly half under the region of totality. This rapid modification of conductivity on the dayside has been associated with magnetosphere-ionosphere waves observed in both hemispheres during a high latitude eclipse (Coyle et al, 2023). It is possible that these dayside magnetosphere waves couple to a fast-mode wave that travels toward the magnetotail.…”
Section: Discussionmentioning
confidence: 88%
“…It is likely that future modeling work may give us an insight into the plausibility of coupling energy from the dayside to the nightside in a manner that can trigger a substorm. Coyle et al (2023) presented a case study of an Antarctic total solar eclipse and used event data to simulate the amount of energy diverted from the ionosphere in a simple circuit model as in Boström (1974). This analysis yielded a result similar to the energy supposed by Akasofu (2021) necessary to initiate a substorm onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum TEC enhancement was at all sites after the eclipse day. Coyle et al [50] compared GPS TEC observations to the TIE-GCM model ionosphere. They used ground magnetometer observations located along the 40 • magnetic meridian between 69 • S and 79 • S and their magnetically conjugate counterpart.…”
Section: Introductionmentioning
confidence: 99%